Prevalence of Hypertension and Risk Factors among Adolescent High School Girls - Widayati , Kurniasih; Astutik, Windu; Daryaswanti , Putu Intan; Febianingsih, Ni Putu Eka; Dewi , Ni Luh Made Asri; Sulistyadewi, Ni Putu Eny; Noviyanti, Ni Putu Ayu Wulan (Journal Of Nursing Practice, 2026)
Background: The health of adolescent girls is important. Teenage girls have a vital role in giving birth to a new generation (future mothers). Purpose: The research aimed to determine the description of blood pressure in adolescent girls and to analyze what factors were associated with the incidence of hypertension in adolescent girls. Methods: This research used a cross-sectional method with a descriptive approach. The sample of this research, a total of 1,193 adolescent girls at Jembrana Regency, Bali, Indonesia, from 5 high schools and vocational schools, was selected using purposive sampling. The adolescent girls were 15 to 19 years old with an average age of 16.5 years old. Blood pressure was categorized in children and adolescents by using four categories: normal, pre-hypertension, hypertension I, and hypertension II. Results: The research results on 1,193 adolescent girls showed that the majority of respondents had blood pressure in the normal category, totaling 1,031 individuals (86%). A total of 149 adolescent girls (12%) were in the pre-hypertension category, while stage 1 and stage 2 hypertension were found in 13 respondents (1%). The average systolic blood pressure of respondents was 116.3 mmHg (SD ±12.3), and diastolic blood pressure was 71.3 mmHg (SD ±9.8). The average age of respondents was 16.5 years (SD ±0.7). Bivariate analysis results showed that nutritional status based on BMI and mid-upper arm circumference (MUAC) had a significant relationship with the incidence of hypertension in adolescent girls (p < 0.05). Adolescents with overweight, obesity, and chronic energy deficiency (CED) status were more frequently found in the pre-hypertension and hypertension groups. Conclusions: It was concluded in this research that the majority of adolescent girls at Jembrana Regency, Bali-Indonesia had normal blood pressure. To prevent hypertension, adolescent girls have to maintain their health and change risk factors by optimizing their nutritional status.